Ancient civilizations - Scarre, Christopher; Fagan, Brian M.; Golden, Charles W. (New York : Routledge, 2021)
"Ancient Civilizations offers a comprehensive and straightforward account of the world's first civilizations and how they were discovered, drawing on many avenues of inquiry including archaeological excavations, surveys, laboratory work, highly specialized scientific investigations, and both historical and ethnohistorical records. This book covers the earliest civilizations in Eurasia and the Americas, from Egypt and the Sumerians to the Indus Valley, Shang China, and the Maya. It also addresses subsequent developments in Southwest Asia, moving on to the first Aegean civilizations, Greece and Rome, the first states of sub-Saharan Africa, divine kings and empires in East and Southeast Asia, and the Aztec and Inka empires of Mesoamerica and the Andes. It includes a number of features to support student learning: a wealth of images, including several new illustrations; feature boxes which expand on key sites, finds and written sources; and an extensive guide to further reading. With new perceptions of the origin and collapse of states, including a review of the issue of sustainability, this fifth edition has been extensively updated in the light of spectacular new discoveries and the latest theoretical advances. Examining the world's pre-industrial civilizations from a multidisciplinary perspective and offering a comparative analysis of the field which explores the connections between all civilizations around the world, this volume provides a unique introduction to pre-industrial civilizations in all their brilliant diversity. It will prove invaluable to students of Archaeology"--
The study of civilization -- Theories of states -- Mesopotamia: the first cities (3500-2000 B.C.) -- Egyptian civilization -- South Asia: the Indus civilization -- The first Chinese civilizations -- Mesopotamia and the Levant (2000-1200 B.C.) -- Southwest Asia in the first millennium B.C. -- The first Aegean civilizations -- The Mediterranean world in the first millennium (1000-30 B.C.) -- Imperial Rome -- Northeast Africa: Kush, Meroe, and Aksum -- Sub-Saharan Africa -- Divine kings in Southeast Asia -- Kingdoms and empires in East Asia (770 B.C.-A.D. 700) -- Lowland Mesoamerica -- Highland Mesoamerica -- The foundations of Andean civilization -- Andean States (200 B.C.-A.D. 1534)
Includes bibliographical references and index.
Keywords: Civilization, Ancient; Prehistoric peoples; Antiquities; Excavations (Archaeology)